P115 Screening outcomes of household contacts of multidrug-resistant tuberculosis patients in peshawar, pakistan. (15th November 2016) - Javid, A; Khan, MA; Khan, MA; Mehreen, S; Basit, A; Khan, RA; Ihtesham, M; Ullah, I; Khan, A; Ullah, U
Abstract : Objective: To assess the profile of TB/multidrug-resistant TB (MDR-TB) among household contacts of MDR-TB patients. Methods: Close contacts of MDR-TB patients were traced in the cross-sectional study. Different clinical, radiological and bacteriological were performed to rule out the evidence of TB/MDR-TB. Results: Between January 2012 and December 2012, a total of 200 index MDR-TB patients were initiated on MDR-TB treatment, out of which home visit and contacts screening were conducted for 154 index cases. Of 610 contacts who could be studied, 41 (17.4%) were diagnosed with MDR-TB and 10 (4.2%) had TB. The most common symptoms observed were cough, chest pain and fever. Conclusions: The high incidence of MDR-TB among close contacts emphasise the need for effective contact screening programme of index MDR-TB cases in order to cut the chain of transmission of this disease. References: WHO. Multidrug resistant TB (MDR-TB): 2014 updated global report . Geneva: World Health OrganisationOrganization, 2014. WHO. Global tuberculosis report 2015 . Geneva: World Health OrganisationOrganization, 2015. Khan MA, Mehreen S, Basit A, Khan RA, Javaid A. Predictors of poor outcomes among patients treated for multidrug-resistant tuberculosis at Tertiary Care Hospital in Pakistan. American-Eurasian J Toxicol Sci 2015;7 (3):162–172.